STRATEGI POLITIK CALON ANGGOTA DPRD PEREMPUAN PETAHANA PADA PEMILU SERENTAK TAHUN 2019 DI PROVINSI BALI - Indriani, Ida Ayu Diah; Bandiyah, Bandiyah; Azhar, Muhammad Ali (Jurnal Nawala Politika, 2019)
ABSTRACT   This research examined the Political Strategy of Incumbent Female Regional People’s Representative Assembly (DPRD) Members in Simultaneous Elections 2019 in Bali Province. The Theory used in this research was the theory of Political Strategy by Peter Schroder. This Political Strategy is divided into two, including the Offensive Strategy (expanding the number of voters) and the Defensive Strategy (maintaining the number of voters). The approach used in this research was a qualitative approach with the reseach type of descriptive explanatory with the aim of describing, summarizing the various conditions and situations that arise in the community that is the object of research. Keywords : Strategy, Incumbent, Female, DPRD